Durable metal-enhanced fluorescence flexible platform by in-situ growth of micropatterned Ag nanospheres. (10th April 2021) - Liu, Xiangfu; Wang, Rongwen; Ma, Jinming; Zhang, Jibin; Jiang, Pengfei; Wang, Yao; Tu, Guoli
Abstract: Here, we demonstrate an in-situ growth of micropatterned silver nanospheres (Ag NS) array on transparent polyimide (PI), namely PI-Ag substrate, applied as a flexible platform for metal-enhanced fluorescence (MEF). The scheme proposed here can easily control the grid formation of Ag NSs and the particle size inside, thus achieving patterned fluorescence imaging and MEF efficiency optimization. Meanwhile, the magnitude of enhanced intensity, relying on the distance between Ag NSs and emissive molecules, was systematically investigated by exploring diverse polyethyleneimine (PEI) spacer thickness. Consequently, an optimal enhancement factor of 7.9 and a pattern of grid fluorescence imaging was obtained with an insertion of 10 nm PEI on the PI-Ag (25 nm) platform. Moreover, owing to robust adhesion between Ag NSs and PI film by in-situ growth, this flexible PI-Ag MEF platform maintained a stable MEF efficiency even after taking mechanical bending for 1000 cycles. This new surface-confined micropatterned Ag NSs PI film provides a promising candidate in design flexible MEF platforms for future analytical and clinical sensing applications.